Agricultura orgánica y sostenibilidad: análisis de prácticas agronómicas y disponibilidad de nutrientes en Clark Farm, Massachusetts, Estados Unidos - Jaime-Huaman, Emerson (The Biologist, 2026)
This study evaluated crop diversity, agronomic practices, and soil chemical properties at Clark Farm organic farm, Massachusetts, USA, to analyze their contribution to a sustainable agricultural system. Seven agronomic management components and various soil fertility parameters, including pH, cation exchange capacity, macronutrients, and micronutrients, were analyzed. The results showed that crop diversification and organic practices promote productive stability, biological pest control, and agroecosystem sustainability. However, elevated levels of phosphorus and calcium and marginal micronutrient availability were identified, suggesting the need for balanced nutritional management.